Inovasi Pembelajaran Membaca Bahasa Jepang (Dokkai) melalui Penerapan Task-Based Language Teaching (TBLT) Berbasis Digital - Amira Agustin Kocimaheni; Djodjok Soepardjo; Didik Nurhadi; Him'mawan Adi Nugroho; Lispridona Diner (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This article aims to identify the characteristics of the TBLT approach and its potential integration in learning to read Japanese (dokkai); describe the digitization of learning that can support the effectiveness of TBLT in Japanese reading skills (dokkai); and prepare a conceptual design for the implementation of digital-based TBLT that can be implemented in the context of dokkai learning in higher education. Using a conceptual research approach and literature review, this article provides a theoretical basis and direction for the implementation of digital task-based reading learning. The results show that in the context of dokkai, tasks designed according to the characteristics of the TBLT approach can be activities such as responding to Japanese news by making personal opinions, compiling a summary of a group reading, comparing two informational texts, or compiling a concept map based on the content of the reading. Then the use of digital technology is able to strengthen the implementation of TBLT, especially in the context of reading learning. Technology allows students to access authentic texts in multimodal form (text, videos, infographics), process information collaboratively, and express the results of understanding in creative formats such as blogs, podcasts, or videos. Furthermore, a conceptual model for the application of digital-based TBLT in dokkai learning in higher education was formulated. The model includes five main components: (1) authentic reading task selection, (2) integration of task support technologies, (3) collaboration in task completion, (4) reflection and metacognition, and (5) formative feedback.